GAMBARAN PENGETAHUAN IBU HAMIL TENTANG ASUPAN NUTRISI UNTUK PROSES PERKEMBANGAN BENIH GIGI - Putri Sri Wahyuni; Eliza Herijulianti; Nurul Fatikhah; Ulfah Utami (Poltekkes Kemenkes Bandung, 2022)
Dental and oral health is important for overall health and quality of life so that the oral cavity cannot be separated from its function with other parts of the body. Nutrition is an important thing that must be fulfilled by pregnant women during pregnancy because it can affect the development of the fetus. Adequate nutritional intake is closely related to the formation and development of bones and teeth in the fetus. This study aims to describe the knowledge of pregnant women about nutritional intake for the process of developing tooth seeds in PKM Sumbersari Village, Ciparay District, Bandung Regency. The research method is descriptive. The research was carried out at PKM Sumbersari Village, Ciparay District, Bandung Regency. The study population was pregnant women who came to check their pregnancy at PKM Sumbersari Village, Bandung Regency. Sampling with Accidental Sampling as many as 28 respondents. The results showed that knowledge about nutritional intake for the development process of tooth germ as a whole was 53.6% of respondents had good criteria, and 46.6% had poor criteria. Respondents in this study had good knowledge of nutritional intake for the development of tooth germs.